Factors Causing Indonesian Grammatical Interferences on English Use: A Case of Undergraduate Students’ Expository Writing in Padang, Indonesia - Hermawati Syarif (Proceedings of ISELT FBS Universitas Negeri Padang, 2014)
The interference of the first language (Indonesian) in the use of English as a foreign language is a phenomenon of one’s failure in acquiring the language. The interference may occur on lexical, morphological and syntactical elements which cause by many factors. This paper discusses the factors causing Indonesian grammatical interferences on English use shown in the English students’ writings of the two universities in Padang, Indonesia.   As a whole, the main causes are linguistics and non-linguistics factors which contributed to any grammatical interference appeared in students’ writing concerning syntactical, morphological and lexical elements. Limited vocabulary and lack competence of English were the linguistics factors. The tendency to use such vocabularies caused  grammatical interferences since those vocabularies could not be appropriately used in the contexts of sentences. While the non-linguistic factor contributed to this phenomenon in terms of cultural internalization and social status as well as psychological drive.The influence of Indonesian cultures, such as the use of complicated and twisty sentences appeared on students’ writing instead of being direct to the point as in the English culture. A sort of motivation gained by students, that is intstrumental motivation, may also result interference.